Pengaruh Aktivitas Thin Capitalization Terhadap Penghindaran Pajak - Siti Salwah; Eva Herianti (JRB-Jurnal Riset Bisnis, 2019)
The purpose of this study is to estimate the effect of thin capitalization activities on tax avoidance. The study sample used the consumer goods industry listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017 through purposive sampling and obtained 24 companies, so that 72 observations were obtained. The results showed that thin capitalization had a negative and significant effect on tax avoidance using both the common effect, fixed effect and random effects methods. The implications of this study prove that after the regulation of the finance minister about the ratio of debt to capital affects the value of the debt to capital ratio (DER) to be lower, thereby reducing tax avoidance (book tax gap).